Effects of Asm-024, A Modulator of Acetylcholine Receptor Function, On Airway Responsiveness and Allergen-Induced Responses in Patients with Mild Asthma. Issue 4 (2015) - Boulet, Louis-Philippe; Gauvreau, Gail M; Cockcroft, Donald W; Davis, Beth; Vachon, Luc; Cormier, Yvon; O'Byrne, Paul M
Abstract : OBJECTIVES: To evaluate the safety, tolerability and clinical activity of ASM-024, a new cholinergic compound with dual nicotinic and muscarinic activity, in mild allergic asthma. METHODS: The present study involved 24 stable, mild allergic asthmatic subjects. In a cross-over design, ASM-024 (50 mg or 200 mg) or placebo were administered once daily by nebulization over three periods of nine consecutive days separated by a three-week washout. The effect of each treatment on the forced expiratory volume in 1 s (FEV1 ), provocative concentration of methacholine causing a 20% decline in FEV1 (PC20 ), early and late asthmatic responses, and allergen-induced inflammation were measured. RESULTS: Seventeen subjects completed the study. During treatment with ASM-024 at 50 mg or 200 mg, the PC20 value increased respectively from a mean (± SD) 2.56±3.86 mg/mL to 4.11 mg/mL (P=0.007), and from 3.12±4.37 mg/mL to 5.23 mg/mL (P=0.005) (no change with placebo). On day 7 (day preceding allergen challenge), postdosing FEV1 increased by 2.0% with 50 mg (P=0.005) and 1.9% with 200 mg (P=0.008) (placebo −1.1%). ASM-24 had no inhibitory effect on early and late asthmatic responses, nor on sputum eosinophil or neutrophil levels. ASM-024 induced no serious adverse events, but caused cough in 22% and 48% of the subjects with 50 mg and 200 mg, respectively, compared with 10% who were on placebo. CONCLUSIONS: ASM-024 did not inhibit allergen-induced asthmatic response and related airway inflammation, but reduced methacholine airway responsiveness and slightly improved lung function. The mechanism by which ASM-024 improves these outcomes requires further study.